A new allele, HLA‐DQB1*05:50, identified by sequence‐based typing in a Korean individual. Issue 3 (10th January 2014) - Ko, S.‐Y.; Oh, H.‐B.; Kwon, O.‐J.
<x xml:space="preserve">Abstract</x> The new allele DQB1*05:50 showed one nucleotide difference with DQB1*05:03:01:01 at codon 39 (CGC/CAC).